Outcome following major hepatic resection in the elderly patients - Mastoraki, Aikaterini; Tsakali, Athina; Papanikolaou, Ioannis S.; Danias, Nikolaos; Smyrniotis, Vasilios; Arkadopoulos, Nikolaos (Clinics and research in hepatology and gastroenterology, 2014)
Recent advances in operative techniques, anaesthesiologic management and intensive care have greatly reduced morbidity and mortality of major hepatectomy allowing a progressive broadening of its indications by including patients with chronic liver disorders as well as elderly subjects. It is apparent that with the aging population, more elderly patients are being referred for surgery. Selecting appropriate candidates for surgical resection is therefore crucial to maximize the benefit derived from surgery. Nevertheless, it is not clear whether advanced age itself increases surgical risk or additional age-independent variables are associated with higher operative morbidity. Regardless of the indications for surgery and the extent of planned liver resections, this population is more likely to suffer from relevant disorders. Previous studies on the safety of major liver resections in the elderly patients cite morbidity and mortality rates of approximately 30–40% and 4–5% respectively. In addition, hepatic resections for hepatocellular carcinoma or colorectal liver metastases have been reported as safe in the elderly as in the younger population. Nevertheless, a small number of investigations studied the outcome of major hepatectomy in the population over 70years of age. The aim of our study was to evaluate overall experience with liver resections in the elderly population by comparing the early as well as the long-term outcome of the procedure in 70years and older versus the less than 70 age group and to identify whether the age of patients alone is associated with increased rate and severity of postoperative complications.